2016
DOI: 10.3892/ol.2016.4390
|View full text |Cite
|
Sign up to set email alerts
|

Progestin-releasing intrauterine device insertion plus palliative radiotherapy in frail, elderly uterine cancer patients unfit for radical treatment

Abstract: The present study investigated the combination of levonorgestrel-releasing intrauterine device (LNG-IUD) insertion and palliative radiotherapy (RT) as a potential approach for treating frail, elderly endometrial cancer (EC) patients considered unfit for curative oncological treatments. The inclusion criteria were an age of ≥65 years, pathological confirmation of a uterine neoplasm, a Charlson comorbidity index (CCI) value of ≥4 and the presence of vaginal bleeding. Patients underwent intrauterine insertion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Progestin treatment of patients with atypical hyperplasia has been studied previously, with recent meta-analyses showing disease remission in 66-85.6% patients, and LNG-IUS once again showed better therapeutic results [7,16]. Recent prospective studies have been conducted regarding the treatment of patients with endometrial cancer stage 1a, who were unfit for surgery, with LNG-IUS and concurrent radiotherapy [17] or only LNG-IUS [18]. The former study showed good remission rate with an overall 2-year survival greater than 75% and well-controlled bleeding in all the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Progestin treatment of patients with atypical hyperplasia has been studied previously, with recent meta-analyses showing disease remission in 66-85.6% patients, and LNG-IUS once again showed better therapeutic results [7,16]. Recent prospective studies have been conducted regarding the treatment of patients with endometrial cancer stage 1a, who were unfit for surgery, with LNG-IUS and concurrent radiotherapy [17] or only LNG-IUS [18]. The former study showed good remission rate with an overall 2-year survival greater than 75% and well-controlled bleeding in all the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative radiotherapy exhibits substantial promise in controlling symptoms associated with gynecological cancers. As summarized in Table 2 , studies demonstrate varying success rates in alleviating symptoms like bleeding, pain, and vaginal discharge across different treatment regimens [ 14 , 15 , 18 , 20 , 22 , 23 , 24 , 25 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though treatment of EC by progestin therapy is largely based on studies of younger women desiring future fertility, our study, along with others, suggests there may also be a role for progestin therapy to treat postmenopausal women if RT is not feasible or desired ( Baker et al, 2012 , Staples et al, 2018 ). Macchia and colleagues reported on 9 women aged ≥65 years treated with LNG-IUD followed by palliative radiation (30 Gy) and showed a high bleeding remission rate of 88.8% ( Macchia et al, 2016 ). Median follow-up was 20 months, but they did not report recurrence or survival data.…”
Section: Discussionmentioning
confidence: 99%